Reframing social entrepreneurship in IB: from institutional constraints to generative processes in Creation Theory - Alvarez, Sharon A. (Journal of International Business Studies, 2026)
Stephan, Uhlaner, and Stride’s (J Int Bus Stud 46:308–331, 2015) Decade Award-winning paper highlights how formal and informal institutional antecedents shape the emergence of social entrepreneurship across borders, while their 2026 retrospective extended attention to the enduring impact of social ventures. The Reuber and Fischer (J Int Bus Stud, 2026) commentary extended the conversation to emphasize the organizational impact of social ventures. Yet, while the retrospective and Reuber and Fischer’s (J Int Bus Stud, 2026) commentary emphasize how social ventures evolve and generate impact over time, they stop short of fully exploring how entrepreneurial action itself brings institutions and stakeholders into being. This commentary builds on the award-winning paper, the retrospective, and Reuber and Fischer’s commentary, while drawing on Creation Theory (Alvarez and Barney in Strateg Entrep J 1:11–26, 2007; Alvarez and Sachs in Acad Manag Rev 48:187–202, 2023) to reframe social entrepreneurship as a generative process in which opportunities, institutions, and stakeholders emerge together through cycles of action, interpretation, and shared experience under conditions of uncertainty. This perspective shows how entrepreneurs and stakeholders not only adapt to institutional environments but also actively create and reconfigure them. This reframing opens new directions: examining how entrepreneurial processes generate novel institutional forms across borders, how stakeholder roles are negotiated and renegotiated across cultural contexts, and how social ventures reshape the very landscapes in which they operate.